2018
DOI: 10.3390/microorganisms6040116
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion Body Bead Size in E. coli Controlled by Physiological Feeding

Abstract: The Gram-negative bacterium E. coli is the host of choice for producing a multitude of recombinant proteins relevant in the pharmaceutical industry. Generally, cultivation is easy, media are cheap, and a high product titer can be obtained. However, harsh induction procedures combined with the usage of IPTG (isopropyl β-d-1 thiogalactopyranoside) as an inducer are often believed to cause stress reactions, leading to intracellular protein aggregates, which are so known as so-called inclusion bodies (IBs). Downst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 47 publications
2
18
0
Order By: Relevance
“…Nevertheless, the found IB content of around 30% in the biomass stood in good agreement with recent findings in our research group. We have shown that the maximum intracellular IB size varied between 500 and 700 nm [16], which resembles a ratio around 30% of IB per cell given the rough E. coli size estimation of 2 µm. Furthermore, the basic and cheap refolding with glycerol as single additive in deionized water resulted in a refolding yield of around 30% compared to ~ 49% [39] or 32.3% [35] for similar proteins in more complex buffers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the found IB content of around 30% in the biomass stood in good agreement with recent findings in our research group. We have shown that the maximum intracellular IB size varied between 500 and 700 nm [16], which resembles a ratio around 30% of IB per cell given the rough E. coli size estimation of 2 µm. Furthermore, the basic and cheap refolding with glycerol as single additive in deionized water resulted in a refolding yield of around 30% compared to ~ 49% [39] or 32.3% [35] for similar proteins in more complex buffers.…”
Section: Discussionmentioning
confidence: 99%
“…IBs are formed in the cytosol of E. coli and they usually consist of aggregated, insoluble target protein that is misfolded or partially unfolded, leading to no or reduced activity [12, 13]. Their formation is mostly dependent on the used promoter system and strength [14], the target protein class [12], and the process conditions [15, 16]. However, the misfolded/unfolded character of IBs makes formation kinetics, size distributions in the cytosol, and IB purity comparable between similar protein classes (e.g., [15, 17]) until the initial IB solubilisation procedure, in which protein specific conditions have to be considered.…”
Section: Introductionmentioning
confidence: 99%
“…During the induction period, samples were taken in a maximum of 120 min intervals and analyzed subsequently. Details on the process analytics can be found elsewhere ( Kopp et al, 2018 ; Slouka et al, 2018 ). For chemostat cultivations samples were collected after batch and afterward once or, if necessary, twice a day.…”
Section: Methodsmentioning
confidence: 99%
“…Soluble protein samples were filtered (0.2 μm mesh) and directly used in the HPLC. Inclusion Body (IB) pellet samples were prepared according to Kopp et al (2018) , and subsequently solubilized using following buffer: 7.5 M guanidine hydrochloride, 62 mM Tris at pH = 8 and 125 mM DTT was added right before use. The filtered IB samples were quantified by HPLC analysis (UltiMate 3000; Thermo Fisher, Waltham, MA, United States).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, CatIB size might be an important parameter for CatIB application. As shown by Kopp et al (2018) for conventional, inactive IBs, the size of IBs can be adjusted by nutrient feeding. This strategy might also be applicable for CatIB production to optimize the specific activity of CatIBs.…”
Section: Important Process Parameters For Catib Productionmentioning
confidence: 99%